Double-layer solid electrolyte membrane, preparation method thereof and all-solid-state battery

By using a double-layer solid electrolyte membrane in an all-solid state battery, the negative electrode and positive electrode are stabilized by hydride and halide solid electrolyte layers respectively, the side reaction problems caused by a single solid electrolyte are solved, and the coulomb efficiency and cycle stability of the battery are significantly improved.

CN119627200AActive Publication Date: 2025-03-14ZHEJIANG BAIMA LAKE LABORATORY CO LTD

Patent Information

Application Number
CN202510152165.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-12
Publication Date
2025-03-14
Estimated Expiration
2045-02-12

AI Technical Summary

Technical Problem

A single solid electrolyte is prone to strong side reactions at the positive or negative electrode interface during the battery cycle, resulting in rapid attenuation of the battery capacity.

Method used

A double-layer solid electrolyte membrane is used, the first layer is a hydride solid electrolyte, and the second layer is a halide solid electrolyte. The crystal structure stability is improved through P and S dual substitutions to reduce interfacial side reactions.

Benefits of technology

It improves the Coulomb efficiency and cycle stability of solid-state batteries and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627200A_ABST
    Figure CN119627200A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of solid electrolyte, and discloses a double-layer solid electrolyte membrane, a preparation method thereof and an all-solid-state battery. The double-layer solid-state electrolyte membrane comprises a first solid-state electrolyte layer and a second solid-state electrolyte layer which are overlapped with each other, the first solid-state electrolyte layer comprises hydride solid-state electrolyte, and the second solid-state electrolyte layer comprises halide solid-state electrolyte; the hydride solid electrolyte comprises Li < 7-a > P (BH4) S < 6-a > and / or Li < 7-a-b > P (BH4) S < 6-a-b > X , a < = 2, 0lt; blt; 2. The interface between the double-layer solid-state electrolyte membrane and the positive electrode and the interface between the double-layer solid-state electrolyte membrane and the negative electrode have good interface stability, and the interface side reaction between the two solid-state electrolyte layers is less, so that the solid-state battery has high coulombic efficiency and cycling stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of solid electrolyte technology, and in particular to a double-layer solid electrolyte membrane and a preparation method thereof, and an all-solid-state battery. Background Art

[0002] With the gradual increase in the penetration rate of electric vehicles and the continuous expansion of grid energy storage, battery safety and energy density have received special attention as key indicators for practical applications. All-solid-state batteries use solid electrolytes to replace the separators and flammable liquid electrolytes in traditional liquid batteries, which is expected to improve battery safety. At the same time, compared with liquid batteries, all-solid-state batteries are more compatible with thick electrode technology, which helps to increase the mass proportion of active materials in the battery, thereby improving the battery energy density.

[0003] An ideal solid electrolyte needs to have characteristics such as high ionic conductivity, low electronic conductivity, wide electrochemical window, and high chemical stability. Generally speaking, solid electrolytes can combine crystal structure design and ion doping to achieve performance indicators of high ionic conductivity and low electronic conductivity, such as doping halogen anions in hydride solid electrolytes and doping transition metal cations in sulfide and halide solid electrolytes. However, due to the physicochemical properties of the materials, solid electrolytes usually do not have a wide electrochemical window and cannot take into account both high-potential positive electrode materials and low-potential negative electrode materials at the same time. During the battery cycle, under the multiple effects of electrochemistry, chemistry, and thermodynamics, a single solid electrolyte is prone to strong side reactions at the positive or negative electrode interface, resulting in rapid attenuation of the battery capacity, such as hydrides and sulfides are easy to decompose at high potentials, sulfides are unstable to lithium metal, and halides are easy to be reduced at low potentials. Summary of the invention

[0004] In order to solve the technical problem that a single solid electrolyte is prone to strong side reactions at the positive or negative electrode interface, resulting in rapid attenuation of battery capacity, the present invention provides a double-layer solid electrolyte membrane and a preparation method thereof, and an all-solid-state battery. The double-layer solid electrolyte membrane of the present invention has good interface stability at the interface between the positive and negative electrodes, and there are fewer interface side reactions between the two solid electrolyte layers, which can enable the solid-state battery to have higher coulombic efficiency and cycle stability.

[0005] The specific technical scheme of the present invention is: In a first aspect, the present invention provides a double-layer solid electrolyte membrane, comprising a first solid electrolyte layer and a second solid electrolyte layer stacked on each other; the first solid electrolyte layer comprises a hydride solid electrolyte, and the second solid electrolyte layer comprises a halide solid electrolyte; the hydride solid electrolyte comprises Li 7-a P(BH4) a S 6-a and / or Li 7-a-bP(BH4) a S 6-a-b X b , where X is a halogen, 0 <a≤2,0<b<2。

[0006] In the double-layer solid electrolyte membrane of the present invention, the hydride solid electrolyte has good low-potential stability and stability to the negative electrode, so that the first solid electrolyte layer can directly contact the negative electrode; the halide solid electrolyte has good high-potential stability and stability to the positive electrode, so that the second solid electrolyte layer can directly contact the positive electrode. In the above manner, the design of the double-layer solid electrolyte membrane in the present invention can solve the problem that a single type of solid electrolyte cannot be compatible with both positive and negative electrodes, improve the interface stability between the solid electrolyte membrane and the electrode, and thus improve the coulombic efficiency and cycle stability of the battery.

[0007] The hydride solid electrolyte contains negative hydrogen ions, which have strong reducing properties, and the halide solid electrolyte contains high-valent metal ions, which leads to direct contact between the two solid electrolytes at the interface between the first and second solid electrolyte layers, resulting in interface side reactions, thereby reducing the lithium ion transmission rate, resulting in poor coulombic efficiency and cycle stability of the battery. 7-a P(BH4) a S 6-a and / or Li 7-a-b P(BH4) a S 6-a-b X b As a hydride solid electrolyte, the double substitution of P and S can reduce the density of hydrogen anions in the unit cell, improve the stability of the crystal structure, weaken the reducibility of the electrolyte, thereby improving the compatibility of the hydride electrolyte and the halide electrolyte, reducing the interface side reactions, and helping to improve the coulombic efficiency and cycle stability of the battery. In addition, although halogen ion substitution can also reduce the density of hydrogen anions in the hydride electrolyte unit cell, compared with the use of halogen ion substitution alone, the present invention introduces P and S double substitution, which can form PS4 in the crystal structure. 3- Anion, with BH4 - The anions also have a tetrahedral structure, and are larger in size, have a higher charge number, and a more stable anion configuration. Therefore, they can more effectively improve the stability of the crystal structure, weaken the reducibility of the electrolyte, and thus better improve the interface compatibility between the double-layer electrolytes, thereby improving the coulombic efficiency and cycle stability of the battery to a greater extent.

[0008] Preferably, the halide solid electrolyte comprises Li c Z d , wherein M is at least one of Zr, Hf, Sc, In, Y, La, Nb and Gd, Z is at least one of F, Cl and I, 1≤c≤8, 2≤d≤10.

[0009] Preferably, the Li 7-a-b P(BH4) a S 6-a-b X b wherein X is at least one of F, Cl and I.

[0010] Preferably, in the first solid electrolyte layer, the mass proportion of the hydride solid electrolyte is not less than 90%; in the second solid electrolyte layer, the mass proportion of the halide solid electrolyte is not less than 90%.

[0011] Furthermore, in the first solid electrolyte layer, the mass proportion of the hydride solid electrolyte is 90-99.8%; in the second solid electrolyte layer, the mass proportion of the halide solid electrolyte is 90-99.8%.

[0012] Furthermore, in the first solid electrolyte layer, the mass proportion of the hydride solid electrolyte is 95-99.8%; in the second solid electrolyte layer, the mass proportion of the halide solid electrolyte is 95-99.8%.

[0013] Preferably, the first solid electrolyte layer and the second solid electrolyte layer further include a polymer binder.

[0014] Further, the polymer binder includes at least one of styrene-butadiene rubber (SBR), nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), polymethyl methacrylate (PMMA), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), styrene-butadiene block copolymer (SBS), styrene-ethylene-butylene-styrene block copolymer (SEBS) and polyisobutylene (PIB).

[0015] In a second aspect, the present invention provides a method for preparing the double-layer solid electrolyte membrane, comprising the following steps: S1: mixing the polymer binder used in the first solid electrolyte layer with an inert solvent to obtain a first glue solution; S2: mixing the first glue, the hydride solid electrolyte and the inert solvent, coating the mixture on the substrate, and drying the mixture to form a first solid electrolyte layer; S3: mixing the polymer binder used in the second solid electrolyte layer with an inert solvent to obtain a second glue solution; S4: Mix the second glue solution, the halide solid electrolyte and the inert solvent, apply the mixture on the first solid electrolyte layer, and dry the mixture to obtain a double-layer solid electrolyte membrane.

[0016] Preferably, in steps S1 to S4, the inert solvent includes at least one of toluene, p-xylene, 1,3,5-trimethylbenzene, chlorobenzene, n-hexane, n-heptane, dichloromethane and dichloroethane; the inert solvents in steps S1 to S4 may be the same or different.

[0017] Preferably, in step S2, the substrate is copper foil, aluminum foil, stainless steel foil, polyethylene terephthalate (PET) substrate, polyethylene (PE) substrate, polyimide (PI) substrate, polytetrafluoroethylene (PTFE) substrate or release paper.

[0018] Preferably, in steps S2 and S4, the drying process includes air drying and vacuum drying.

[0019] In a third aspect, the present invention provides an all-solid-state battery, comprising the double-layer solid electrolyte membrane, a positive electrode and a negative electrode; the first solid electrolyte layer is in contact with the negative electrode, and the second solid electrolyte layer is in contact with the positive electrode.

[0020] Preferably, the active material of the negative electrode includes at least one of silicon, silicon monoxide, silicon oxide, aluminum silicon alloy, lithium metal, lithium indium alloy, lithium tin alloy and lithium aluminum alloy.

[0021] Furthermore, the active material of the negative electrode includes at least one of silicon, aluminum-silicon alloy, lithium metal and lithium-indium alloy.

[0022] Preferably, the active material of the positive electrode includes at least one of lithium cobalt oxide, lithium manganese oxide, nickel cobalt manganese (NCM) ternary material, nickel cobalt aluminum (NCA) ternary material, lithium iron phosphate, lithium iron manganese phosphate, sulfur, selenium, iron sulfide and sulfided polyacrylonitrile.

[0023] Furthermore, the active material of the positive electrode includes at least one of lithium cobalt oxide, nickel cobalt manganese (NCM) ternary material, lithium iron manganese phosphate, sulfur and sulfurized polyacrylonitrile.

[0024] Compared with the prior art, the present invention has the following advantages: (1) The present invention uses a specific first solid electrolyte layer and a second solid electrolyte layer to form a double-layer solid electrolyte membrane, which can ensure good interface stability between the solid electrolyte and the positive and negative electrodes, thereby giving the solid-state battery higher coulombic efficiency and cycle stability; (2) The present invention uses Li in the first solid electrolyte layer 7-a P(BH4) a S 6-a and / or Li 7-a-b P(BH4) a S 6-a-b X bAs a hydride solid electrolyte, it can reduce the interface side reactions between the first and second solid electrolyte layers, thereby improving the coulombic efficiency and cycle stability of the solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 A schematic diagram of the structure of the all-solid-state battery in the present invention.

[0026] The reference numerals in the drawings are: positive electrode current collector 1 , positive electrode 2 , double-layer solid electrolyte membrane 3 , second solid electrolyte layer 31 , first solid electrolyte layer 32 , negative electrode 4 , negative electrode current collector 5 . DETAILED DESCRIPTION

[0027] The present invention will be further described below in conjunction with the embodiments.

[0028] First, the present invention relates to a double-layer solid electrolyte membrane, comprising a first solid electrolyte layer and a second solid electrolyte layer stacked on each other; the first solid electrolyte layer comprises a hydride solid electrolyte, and the second solid electrolyte layer comprises a halide solid electrolyte; the hydride solid electrolyte comprises Li 7-a P(BH4) a S 6-a and / or Li 7-a-b P(BH4) a S 6-a- b X b , where X is a halogen, 0 <a≤2,0<b<2。

[0029] In some specific embodiments, the Li 7-a-b P(BH4) a S 6-a-b X b wherein X is at least one of F, Cl and I.

[0030] In some specific embodiments, the halide solid electrolyte includes Li c Z d , wherein M is at least one of Zr, Hf, Sc, In, Y, La, Nb and Gd, Z is at least one of F, Cl and I, 1≤c≤8, 2≤d≤10.

[0031] In some specific embodiments, in the first solid electrolyte layer, the mass proportion of the hydride solid electrolyte is not less than 90%; in the second solid electrolyte layer, the mass proportion of the halide solid electrolyte is not less than 90%.

[0032] In some specific embodiments, the first solid electrolyte layer and the second solid electrolyte layer further include a polymer binder. Optionally or preferably, the polymer binder includes at least one of styrene-butadiene rubber (SBR), nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), polymethyl methacrylate (PMMA), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), styrene-butadiene block copolymer (SBS), styrene-ethylene-butylene-styrene block copolymer (SEBS) and polyisobutylene (PIB).

[0033] Second, the present invention relates to a method for preparing the double-layer solid electrolyte membrane, comprising the following steps: S1: mixing the polymer binder used in the first solid electrolyte layer with an inert solvent to obtain a first glue solution; S2: mixing the first glue, the hydride solid electrolyte and the inert solvent, coating the mixture on the substrate, and drying the mixture to form a first solid electrolyte layer; S3: mixing the polymer binder used in the second solid electrolyte layer with an inert solvent to obtain a second glue solution; S4: Mix the second glue solution, the halide solid electrolyte and the inert solvent, apply the mixture on the first solid electrolyte layer, and dry the mixture to obtain a double-layer solid electrolyte membrane.

[0034] In some specific embodiments, in steps S1 to S4, the inert solvent includes at least one of toluene, p-xylene, 1,3,5-trimethylbenzene, chlorobenzene, n-hexane, n-heptane, dichloromethane and dichloroethane; the inert solvents in steps S1 to S4 may be the same or different.

[0035] In some specific embodiments, in step S2, the substrate is copper foil, aluminum foil, stainless steel foil, polyethylene terephthalate (PET) substrate, polyethylene (PE) substrate, polyimide (PI) substrate, polytetrafluoroethylene (PTFE) substrate or release paper.

[0036] In some specific embodiments, in steps S2 and S4, the drying process includes air drying and vacuum drying.

[0037] Third, the present invention relates to an all-solid-state battery, comprising the double-layer solid electrolyte membrane, a positive electrode and a negative electrode; the first solid electrolyte layer is in contact with the negative electrode, and the second solid electrolyte layer is in contact with the positive electrode.

[0038] In some specific embodiments, the active material of the negative electrode includes at least one of silicon, silicon monoxide, silicon oxide, aluminum silicon alloy, lithium metal, lithium indium alloy, lithium tin alloy and lithium aluminum alloy.

[0039] In some specific embodiments, the active material of the positive electrode includes at least one of lithium cobalt oxide, lithium manganese oxide, nickel cobalt manganese (NCM) ternary material, nickel cobalt aluminum (NCA) ternary material, lithium iron phosphate, lithium iron manganese phosphate, sulfur, selenium, iron sulfide and sulfided polyacrylonitrile.

[0040] The present invention is described below by specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Without departing from the spirit and scope of the inventive concept, changes and advantages that can be thought of by those skilled in the art are included in the present invention, and the attached claims and any equivalents thereof are the protection scope of the present invention.

[0041] Unless otherwise defined, all technical terms and scientific terms used in the present invention have the same meanings as those commonly understood by ordinary technicians in the field to which the present disclosure belongs. Unless otherwise specified, the raw materials and equipment used in the present invention are conventional raw materials and equipment in the field and can be obtained from conventional commercial channels; unless otherwise specified, the methods used in the present invention are conventional methods in the field.

[0042] Example 1 The double-layer solid electrolyte membrane of this embodiment is prepared according to the following steps: S1: Add SBR to p-xylene and mix well to obtain a first glue solution, wherein the mass ratio of SBR to p-xylene is 4:96.

[0043] S2: Add the first colloid and the hydride solid electrolyte Li5P(BH4)2S4 into p-xylene, stir mechanically to obtain a first electrolyte slurry, wherein the mass ratio of the first colloid, Li5P(BH4)2S4 and p-xylene is 50:98:300.

[0044] S3: coating the first electrolyte slurry on the PET substrate, drying it at 40° C. for 2 h, and then drying it again at 60° C. for 10 h in vacuum, thereby forming a first solid electrolyte layer on the PET substrate.

[0045] S3: Add SBR to 1,3,5-trimethylbenzene and mix well to obtain a second glue solution, wherein the mass ratio of SBR to 1,3,5-trimethylbenzene is 2:98.

[0046] S4: Add the second glue and the halide solid electrolyte Li3InCl6 into 1,3,5-trimethylbenzene, and stir them mechanically to obtain a second electrolyte slurry, wherein the mass ratio of the second glue, Li3InCl6 and 1,3,5-trimethylbenzene is 100:98:100.

[0047] S5: coating the second electrolyte slurry on the first solid electrolyte layer, drying it at 40° C. with air blowing for 2 h, and then drying it again at 60° C. in vacuum for 10 h, thereby forming a first solid electrolyte layer on the first solid electrolyte layer to obtain a double-layer solid electrolyte membrane.

[0048] The double-layer solid electrolyte membrane prepared in this embodiment is used to prepare an all-solid-state battery. The structure of the all-solid-state battery is as follows: Figure 1 As shown, specifically as follows: including a positive electrode current collector 1, a positive electrode 2, a double-layer solid electrolyte membrane 3, a negative electrode 4 and a negative electrode current collector 5 stacked in sequence from top to bottom, wherein the double-layer solid electrolyte membrane 3 is composed of a second solid electrolyte layer 31 and a first solid electrolyte layer 32 stacked up and down, the second solid electrolyte layer 31 is attached to the positive electrode 2, the first solid electrolyte layer 32 is attached to the negative electrode 4, the negative electrode current collector 5 is a carbon-coated copper foil, and the positive electrode current collector 1 is a carbon-coated aluminum foil. The all-solid battery of this embodiment is prepared by the following steps: (1) Add nano-silicon, Li5P(BH4)2S4, vapor-grown carbon fiber (VGCF) and SBR in a mass ratio of 70:22:5:3 to p-xylene, mix and slurry and apply it on carbon-coated copper foil. After the p-xylene evaporates naturally, vacuum dry at 90°C for 16 hours to obtain a negative electrode sheet.

[0049] (2) NCM811, Li3InCl6, VGCF and PVDF in a mass ratio of 80:16:2:2 were added to N-methylpyrrolidone (NMP), mixed and homogenized, and then coated on carbon-coated aluminum foil. After NMP volatilized naturally, it was vacuum-dried at 90°C for 12 hours to obtain the positive electrode sheet.

[0050] (3) The double-layer solid electrolyte membrane is transferred to the positive electrode sheet, the PET substrate is removed, and then the negative electrode sheet is attached to one side of the first solid electrolyte layer, and the tabs are welded and vacuum packaged to obtain an all-solid-state battery.

[0051] Example 2 The double-layer solid electrolyte membrane of this embodiment is prepared according to the following steps: S1: adding PMMA to p-xylene and mixing them evenly to obtain a first glue solution, wherein the mass ratio of PMMA to p-xylene is 8:92.

[0052] S2: Add the first colloid and the hydride solid electrolyte Li5P(BH4)2S4 into p-xylene, stir mechanically to obtain a first electrolyte slurry, wherein the mass ratio of the first colloid, Li5P(BH4)2S4 and p-xylene is 50:96:300.

[0053] S3: coating the first electrolyte slurry on the PET substrate, drying it at 40° C. for 2 h, and then drying it again at 60° C. for 10 h in vacuum, thereby forming a first solid electrolyte layer on the PET substrate.

[0054] S3: Add SBR to 1,3,5-trimethylbenzene and mix well to obtain a second glue solution, wherein the mass ratio of SBR to 1,3,5-trimethylbenzene is 2:98.

[0055] S4: Add the second glue and the halide solid electrolyte Li3InCl6 into 1,3,5-trimethylbenzene, and stir them mechanically to obtain a second electrolyte slurry, wherein the mass ratio of the second glue, Li3InCl6 and 1,3,5-trimethylbenzene is 100:98:100.

[0056] S5: coating the second electrolyte slurry on the first solid electrolyte layer, drying it at 40° C. with air blowing for 2 h, and then drying it again at 60° C. in vacuum for 10 h, thereby forming a first solid electrolyte layer on the first solid electrolyte layer to obtain a double-layer solid electrolyte membrane.

[0057] The double-layer solid electrolyte membrane prepared in this embodiment is used to prepare an all-solid-state battery. The structure and preparation method of the all-solid-state battery are the same as those in Example 1.

[0058] Example 3 The double-layer solid electrolyte membrane of this embodiment is prepared according to the following steps: S1: adding SEBS to p-xylene and mixing them evenly to obtain a first glue solution, wherein the mass ratio of SEBS to p-xylene is 4:96.

[0059] S2: Mix the first gel and the hydride solid electrolyte Li5P(BH4) 1.75 S4Cl 0.25 Add to p-xylene and stir evenly to obtain the first electrolyte slurry, wherein the first gel, Li5P(BH4) 1.75 S4Cl 0.25 The mass ratio between para-xylene and is 50:98:300.

[0060] S3: coating the first electrolyte slurry on the PET substrate, drying it at 40° C. for 2 h, and then drying it again at 60° C. for 10 h in vacuum, thereby forming a first solid electrolyte layer on the PET substrate.

[0061] S3: Add SEBS to 1,3,5-trimethylbenzene and mix well to obtain a second glue solution, wherein the mass ratio of SEBS to 1,3,5-trimethylbenzene is 2:98.

[0062] S4: adding the second colloid and the halide solid electrolyte Li2ZrCl6 into 1,3,5-trimethylbenzene, and mechanically stirring them to obtain a second electrolyte slurry, wherein the mass ratio of the second colloid, Li2ZrCl6 and 1,3,5-trimethylbenzene is 100:98:100.

[0063] S5: coating the second electrolyte slurry on the first solid electrolyte layer, drying it at 40° C. with air blowing for 2 h, and then drying it again at 60° C. in vacuum for 10 h, thereby forming a first solid electrolyte layer on the first solid electrolyte layer to obtain a double-layer solid electrolyte membrane.

[0064] The double-layer solid electrolyte membrane prepared in this example is used to prepare an all-solid-state battery. The structure of the all-solid-state battery is the same as that of Example 1 and is prepared by the following steps: (1) Mix nano-silicon and Li5P(BH4) with a mass ratio of 70:22:5:3 1.75 S4Cl 0.25 , VGCF and SBR are added to p-xylene, mixed and homogenized, and then coated on the carbon-coated copper foil. After the p-xylene is naturally volatilized, it is vacuum-dried at 90°C for 16 hours to obtain the negative electrode sheet.

[0065] (2) Add NCM811, Li2ZrCl6, VGCF and PVDF in a mass ratio of 80:16:2:2 to NMP, mix and slurry and apply it on carbon-coated aluminum foil. After NMP evaporates naturally, dry it in vacuum at 90°C for 12 hours to obtain the positive electrode sheet.

[0066] (3) The double-layer solid electrolyte membrane is transferred to the positive electrode sheet, the PET substrate is removed, and then the negative electrode sheet is attached to one side of the first solid electrolyte layer, and the tabs are welded and vacuum packaged to obtain an all-solid-state battery.

[0067] Example 4 The preparation process of the double-layer solid electrolyte membrane of this embodiment refers to that of embodiment 1, and the only difference from embodiment 1 is that in this embodiment, Li5P(BH4)2S4 is replaced by Li5P(BH4)2S4 in the first solid electrolyte layer. 1.75 S4Cl 0.25 Specifically, the solid electrolyte membrane of this embodiment is prepared according to the following steps: S1: Add SBR to p-xylene and mix well to obtain a first glue solution, wherein the mass ratio of SBR to p-xylene is 4:96.

[0068] S2: Mix the first gel and the hydride solid electrolyte Li5P(BH4) 1.75 S4Cl 0.25 Add to p-xylene and stir evenly to obtain the first electrolyte slurry, wherein the first gel, Li5P(BH4) 1.75S4Cl 0.25 The mass ratio between para-xylene and is 50:98:300.

[0069] S3: coating the first electrolyte slurry on the PET substrate, drying it at 40° C. for 2 h, and then drying it again at 60° C. for 10 h in vacuum, thereby forming a first solid electrolyte layer on the PET substrate.

[0070] S3: Add SBR to 1,3,5-trimethylbenzene and mix well to obtain a second glue solution, wherein the mass ratio of SBR to 1,3,5-trimethylbenzene is 2:98.

[0071] S4: Add the second glue and the halide solid electrolyte Li3InCl6 into 1,3,5-trimethylbenzene, and stir them mechanically to obtain a second electrolyte slurry, wherein the mass ratio of the second glue, Li3InCl6 and 1,3,5-trimethylbenzene is 100:98:100.

[0072] S5: coating the second electrolyte slurry on the first solid electrolyte layer, drying it at 40° C. with air blowing for 2 h, and then drying it again at 60° C. in vacuum for 10 h, thereby forming a first solid electrolyte layer on the first solid electrolyte layer to obtain a double-layer solid electrolyte membrane.

[0073] The double-layer solid electrolyte membrane prepared in this embodiment is used to prepare an all-solid-state battery. The structure and preparation method of the all-solid-state battery are the same as those in Example 1.

[0074] Comparative Example 1 The solid electrolyte membrane preparation process of this comparative example refers to Example 1, and the only difference from Example 1 is that the solid electrolyte membrane of this comparative example is composed of only the first solid electrolyte layer and does not contain the second solid electrolyte layer. Specifically, the solid electrolyte membrane of this comparative example is prepared according to the following steps: S1: Add SBR to p-xylene, mix well, and obtain a glue solution, wherein the mass ratio of SBR to p-xylene is 4:96.

[0075] S2: Add the glue and the hydride solid electrolyte Li5P(BH4)2S4 into p-xylene, stir mechanically to obtain an electrolyte slurry, wherein the mass ratio of the glue, Li5P(BH4)2S4 and p-xylene is 50:98:300.

[0076] S3: coating the electrolyte slurry on a PET substrate, drying it under 40° C. air blowing for 2 h, and then drying it again under 60° C. vacuum drying for 10 h, thereby forming a solid electrolyte layer on the PET substrate to obtain a solid electrolyte membrane.

[0077] The double-layer solid electrolyte membrane prepared in this comparative example was used to prepare an all-solid-state battery. The structure and preparation method of the all-solid-state battery differed from those of Example 1 only in that the double-layer solid electrolyte membrane was replaced with the solid electrolyte membrane in this comparative example, and the two sides of the solid electrolyte membrane were respectively attached to the positive electrode and the negative electrode.

[0078] Comparative Example 2 The solid electrolyte membrane preparation process of this comparative example refers to Example 1, and the only difference from Example 1 is that the solid electrolyte membrane of this comparative example is composed of only the second solid electrolyte layer and does not contain the first solid electrolyte layer. Specifically, the solid electrolyte membrane of this comparative example is prepared according to the following steps: S1: Add SBR to 1,3,5-trimethylbenzene and mix well to obtain a glue solution, wherein the mass ratio of SBR to 1,3,5-trimethylbenzene is 2:98.

[0079] S2: Add the glue and the halide solid electrolyte Li3InCl6 into 1,3,5-trimethylbenzene, and stir them mechanically to obtain an electrolyte slurry, wherein the mass ratio of the glue, Li3InCl6 and 1,3,5-trimethylbenzene is 100:98:100.

[0080] S3: coating the electrolyte slurry on a PET substrate, drying it under 40° C. air blowing for 2 h, and then drying it again under 60° C. vacuum drying for 10 h, thereby forming a solid electrolyte layer on the PET substrate to obtain a solid electrolyte membrane.

[0081] The double-layer solid electrolyte membrane prepared in this comparative example was used to prepare an all-solid-state battery. The structure and preparation method of the all-solid-state battery differed from those of Example 1 only in that the double-layer solid electrolyte membrane was replaced with the solid electrolyte membrane in this comparative example, and the two sides of the solid electrolyte membrane were respectively attached to the positive electrode and the negative electrode.

[0082] Comparative Example 3 The preparation process of the double-layer solid electrolyte membrane of this comparative example is similar to that of Example 1, and the only difference from Example 1 is that in this comparative example, Li5P(BH4)2S4 is replaced by LiBH4 in the first solid electrolyte layer. Specifically, the solid electrolyte membrane of this comparative example is prepared according to the following steps: S1: Add SBR to p-xylene and mix well to obtain a first glue solution, wherein the mass ratio of SBR to p-xylene is 4:96.

[0083] S2: adding the first colloid and the hydride solid electrolyte LiBH4 into p-xylene, and mechanically stirring them to obtain a first electrolyte slurry, wherein the mass ratio of the first colloid, LiBH4 and p-xylene is 50:98:300.

[0084] S3: coating the first electrolyte slurry on the PET substrate, drying it at 40° C. for 2 h, and then drying it again at 60° C. for 10 h in vacuum, thereby forming a first solid electrolyte layer on the PET substrate.

[0085] S3: Add SBR to 1,3,5-trimethylbenzene and mix well to obtain a second glue solution, wherein the mass ratio of SBR to 1,3,5-trimethylbenzene is 2:98.

[0086] S4: Add the second glue and the halide solid electrolyte Li3InCl6 into 1,3,5-trimethylbenzene, and stir them mechanically to obtain a second electrolyte slurry, wherein the mass ratio of the second glue, Li3InCl6 and 1,3,5-trimethylbenzene is 100:98:100.

[0087] S5: coating the second electrolyte slurry on the first solid electrolyte layer, drying it at 40° C. with air blowing for 2 h, and then drying it again at 60° C. in vacuum for 10 h, thereby forming a first solid electrolyte layer on the first solid electrolyte layer to obtain a double-layer solid electrolyte membrane.

[0088] The double-layer solid electrolyte membrane prepared in this comparative example is used to prepare an all-solid-state battery. The structure and preparation method of the all-solid-state battery are the same as those in Example 1.

[0089] Comparative Example 4 The preparation process of the double-layer solid electrolyte membrane of this comparative example refers to Example 1, and the difference from Example 1 is that in this comparative example, Li5P(BH4)2S4 is replaced by Li(BH4) in the first solid electrolyte layer. 0.75 I 0.25 Specifically, the solid electrolyte membrane of this comparative example is prepared according to the following steps: S1: Add SBR to p-xylene and mix well to obtain a first glue solution, wherein the mass ratio of SBR to p-xylene is 4:96.

[0090] S2: Mix the first gel and the hydride solid electrolyte Li(BH4) 0.75 I 0.25 Add to p-xylene and stir evenly to obtain the first electrolyte slurry, wherein the first gel, Li(BH4) 0.75 I 0.25 The mass ratio between para-xylene and is 50:98:300.

[0091] S3: coating the first electrolyte slurry on the PET substrate, drying it at 40° C. for 2 h, and then drying it again at 60° C. for 10 h in vacuum, thereby forming a first solid electrolyte layer on the PET substrate.

[0092] S3: Add SBR to 1,3,5-trimethylbenzene and mix well to obtain a second glue solution, wherein the mass ratio of SBR to 1,3,5-trimethylbenzene is 2:98.

[0093] S4: Add the second glue and the halide solid electrolyte Li3InCl6 into 1,3,5-trimethylbenzene, and stir them mechanically to obtain a second electrolyte slurry, wherein the mass ratio of the second glue, Li3InCl6 and 1,3,5-trimethylbenzene is 100:98:100.

[0094] S5: coating the second electrolyte slurry on the first solid electrolyte layer, drying it at 40° C. with air blowing for 2 h, and then drying it again at 60° C. in vacuum for 10 h, thereby forming a first solid electrolyte layer on the first solid electrolyte layer to obtain a double-layer solid electrolyte membrane.

[0095] The double-layer solid electrolyte membrane prepared in this comparative example is used to prepare an all-solid-state battery. The structure and preparation method of the all-solid-state battery are the same as those in Example 1.

[0096] Comparative Example 5 The preparation process of the double-layer solid electrolyte membrane of this comparative example refers to Example 1, and the difference from Example 1 is that in this comparative example, Li5P(BH4)2S4 is replaced by Li(BH4) in the first solid electrolyte layer. 0.75 Cl 0.25 Specifically, the solid electrolyte membrane of this comparative example is prepared according to the following steps: S1: Add SBR to p-xylene and mix well to obtain a first glue solution, wherein the mass ratio of SBR to p-xylene is 4:96.

[0097] S2: Mix the first gel and the hydride solid electrolyte Li(BH4) 0.75 Cl 0.25 Add to p-xylene and stir evenly to obtain the first electrolyte slurry, wherein the first gel, Li(BH4) 0.75 Cl 0.25 The mass ratio between para-xylene and is 50:98:300.

[0098] S3: coating the first electrolyte slurry on the PET substrate, drying it at 40° C. for 2 h, and then drying it again at 60° C. for 10 h in vacuum, thereby forming a first solid electrolyte layer on the PET substrate.

[0099] S3: Add SBR to 1,3,5-trimethylbenzene and mix well to obtain a second glue solution, wherein the mass ratio of SBR to 1,3,5-trimethylbenzene is 2:98.

[0100] S4: Add the second glue and the halide solid electrolyte Li3InCl6 into 1,3,5-trimethylbenzene, and stir them mechanically to obtain a second electrolyte slurry, wherein the mass ratio of the second glue, Li3InCl6 and 1,3,5-trimethylbenzene is 100:98:100.

[0101] S5: coating the second electrolyte slurry on the first solid electrolyte layer, drying it at 40° C. with air blowing for 2 h, and then drying it again at 60° C. in vacuum for 10 h, thereby forming a first solid electrolyte layer on the first solid electrolyte layer to obtain a double-layer solid electrolyte membrane.

[0102] The double-layer solid electrolyte membrane prepared in this comparative example is used to prepare an all-solid-state battery. The structure and preparation method of the all-solid-state battery are the same as those in Example 1.

[0103] Test Case The all-solid-state batteries prepared in each embodiment and comparative example were subjected to a long cycle performance test under the following test conditions: temperature of 60° C., current of 0.1C, and pressure of 10 MPa. The long cycle performance test results are shown in Table 1.

[0104] Table 1 Long cycle performance test results of all-solid-state batteries

[0105] By analyzing the test results in Table 1, the following conclusions can be drawn: (1) Comparison of Example 1, Comparative Example 1 and Comparative Example 2 shows that compared with the use of a single type of solid electrolyte, the present invention uses a hydride solid electrolyte and a halide solid electrolyte to form a double-layer solid electrolyte membrane, which can improve the coulombic efficiency and cycle stability of the battery. The reason for this is that the hydride solid electrolyte has good low-potential stability and stability to the negative electrode, but is easily decomposed at high potentials, and the halide solid electrolyte has good high-potential stability and stability to the positive electrode, but is easily reduced at low potentials. Therefore, after forming the double-layer structure of the present invention, the solid electrolyte membrane can have good interface stability at the interface between the positive and negative electrodes.

[0106] (2) Comparison of Example 1, Example 4 and Comparative Example 3 shows that compared with the use of LiBH4, when the hydride solid electrolyte uses Li5P(BH4)2S4 or Li5P(BH4) 1.75 S4Cl 0.25 When Li5P(BH4)2S4 and Li5P(BH4)2S4 are used, the battery can have higher coulombic efficiency and cycle stability. 1.75 S4Cl 0.25In the embodiment of the present invention, the double substitution of P and S can reduce the density of hydrogen ions in the unit cell, thereby improving the stability of the crystal structure, weakening the reducibility of the electrolyte, and making the hydride solid electrolyte and the halide solid electrolyte more compatible, thereby reducing the interfacial side reactions between the first and second solid electrolyte layers caused by the strong reducibility of hydrogen ions and the high-valent metal ions in the halide solid electrolyte.

[0107] (3) Comparison of Example 1, Example 4, Comparative Example 4 and Comparative Example 5 shows that compared with the use of Li(BH4) 0.75 I 0.25 and Li(BH4) 0.75 Cl 0.25 For example, when the hydride solid electrolyte uses Li5P(BH4)2S4 or Li5P(BH4) 1.75 S4Cl 0.25 When the battery is replaced by halogen ions, it can achieve higher coulombic efficiency and cycle stability. The reason is that although halogen ion substitution can also reduce the density of hydrogen anions in the hydride electrolyte unit cell, it is still lower than that of Li(BH4) only with halogen ion substitution. 0.75 I 0.25 、Li(BH4) 0.75 Cl 0.25 For example, Li5P(BH4)2S4, Li5P(BH4) 1.75 S4Cl 0.25 Introducing P and S double substitution can form PS4 in the crystal structure 3- Anion, with BH4 - The anions also have a tetrahedral structure, and are larger in size, have a higher charge number, and a more stable anion configuration. Therefore, they can more effectively improve the stability of the crystal structure, weaken the reducibility of the electrolyte, and thus better improve the interface compatibility between double-layer electrolytes.

[0108] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A double-layer solid electrolyte membrane, characterized in that: The invention comprises a first solid electrolyte layer and a second solid electrolyte layer stacked on each other; the first solid electrolyte layer comprises a hydride solid electrolyte, and the second solid electrolyte layer comprises a halide solid electrolyte; the hydride solid electrolyte comprises Li 7-a P(BH4) a S 6-a and / or Li 7-a-b P(BH4) a S 6-a-b X b , where X is a halogen, 0 <a≤2,0<b<2。 2. The double-layer solid electrolyte membrane according to claim 1, characterized in that: The halide solid electrolyte includes Li c Z d , wherein M is at least one of Zr, Hf, Sc, In, Y, La, Nb and Gd, Z is at least one of F, Cl and I, 1≤c≤8, 2≤d≤10.

3. The double-layer solid electrolyte membrane according to claim 1, characterized in that: The Li 7-a-b P(BH4) a S 6-a-b X b wherein X is at least one of F, Cl and I.

4. The double-layer solid electrolyte membrane according to claim 1, characterized in that: In the first solid electrolyte layer, the mass proportion of the hydride solid electrolyte is not less than 90%; in the second solid electrolyte layer, the mass proportion of the halide solid electrolyte is not less than 90%.

5. The double-layer solid electrolyte membrane according to any one of claims 1 to 4, characterized in that: The first solid electrolyte layer and the second solid electrolyte layer further include a polymer binder.

6. A method for preparing a double-layer solid electrolyte membrane according to claim 5, characterized in that: The following steps are involved: S1: mixing the polymer binder used in the first solid electrolyte layer with an inert solvent to obtain a first glue solution; S2: mixing the first glue, the hydride solid electrolyte and the inert solvent, coating the mixture on the substrate, and drying the mixture to form a first solid electrolyte layer; S3: mixing the polymer binder used in the second solid electrolyte layer with an inert solvent to obtain a second glue solution; S4: Mix the second glue solution, the halide solid electrolyte and the inert solvent, apply the mixture on the first solid electrolyte layer, and dry the mixture to obtain a double-layer solid electrolyte membrane.

7. The preparation method according to claim 6, characterized in that: In steps S1 to S4, the inert solvent includes at least one of toluene, p-xylene, 1,3,5-trimethylbenzene, chlorobenzene, n-hexane, n-heptane, dichloromethane and dichloroethane.

8. The preparation method according to claim 6, characterized in that: In step S2, the substrate is copper foil, aluminum foil, stainless steel foil, PET substrate, PE substrate, PI substrate, PTFE substrate or release paper.

9. The preparation method according to claim 6, characterized in that: In steps S2 and S4, the drying process includes air drying and vacuum drying.

10. An all-solid-state battery, characterized in that: It comprises a double-layer solid electrolyte membrane according to any one of claims 1 to 5, a positive electrode and a negative electrode; the first solid electrolyte layer is in contact with the negative electrode, and the second solid electrolyte layer is in contact with the positive electrode.

Citation Information

Patent Citations

  • Binder for all-solid lithium ion secondary battery, electrolyte membrane, electrode membrane, battery, and preparation method

    CN109599561A

  • Solid-state lithium ion battery pre-lithiation electrode and preparation method thereof

    CN113451543A

  • All-solid-state battery and preparation method thereof

    CN113611819A

  • Composite solid electrolyte membrane and preparation method and application thereof

    CN115036563A

  • Preparation method of fluorine element in-situ doped hydroboron-based solid electrolyte

    CN116826154A

Cited By

  • Hydride solid electrolyte membrane, all-solid-state battery and preparation method of all-solid-state battery

    CN119920955A

  • A hydrogenated solid electrolyte membrane, an all-solid-state battery and a preparation method thereof

    CN119920955B

  • Preparation method of double-layer ultrathin electrolyte membrane of all-solid-state battery based on transfer printing technology

    CN120357020A

  • Preparation method of double-layer ultra-thin electrolyte film of all-solid-state battery based on transfer printing technology

    CN120357020B